Some connectivity polynomials and Topological indices of Enhanced Honeycomb Network - Bokhary, Syed Ahtsham Ul Haq; Iqbal, Tanveer (Utilitas Mathematica, 2020)
The M- polynomial is rich in producing closed forms of many degree- based topological indices which correlate chemical properties of the material under investigation. A topological index of graph G is a numerical parameter related to G which characterizes its molecular topology. The theoretical properties of the chemical compounds and their molecular topological indices such as the Zagreb indices, Randi6 index, Symmetric division index, Harmonic index, Inverse sum index, Augmented Zagreb index, etc are correlated. In this par per, the closed form of the Af-polynomial, first Zagreb polynomial, second Zagreb polynomial and Forgotten polynomial of enhanced honeycomb network is computed. Prom the M-polynomial we recover some degree-based topological indices for this network. © 2020 Utilitas Mathematica Publishing Inc.. All rights reserved.